Adapting the women empowerment in agriculture index to specific country context insights and critiques from field work in India - Vemireddy, Vidya (Tata-Cornell Institute for Agriculture and Nutrition, 2019)
Presented by Vidya Vemireddy (TCI), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.